Instrumentation for quantitative analysis of volatile compounds emission at elevated temperatures. Part 1: Design and implementation - Lourenco, Celia; Bergin, Sarah; Hodgkinson, Jane; Francis, Daniel; Staines, Stephen E.; Saffell, John R.; Walton, Christopher; Tatam, Ralph P. (Cranfield University, 2020)
Data to support manuscript Part 1.
Keywords: Polymer-matrix composites (PMCs)'; 'Thermal analysis measurements'; 'Gas emissions'; 'Gas Sensors'; 'Chemical Characterisation of Materials'